2011
DOI: 10.1115/1.4004430
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation Into the Heat Transfer Study of Nanofluids in Microchannel

Abstract: There are very few detailed experimental investigations about the heat transfer behavior of nanofluids in microchannel. The heat transfer behavior of nanofluids in microchannel is investigated. Two microchannels with hydraulic diameters 218 and 303 μm are fabricated by wet etching process on silicon wafer. An experimental set-up having provision of flow in the channel and temperature measurement along with bottom wall temperature is built-up. Alumina nanofluids with concentrations of 0.25 vol. %, 0.5 vol. %, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…U has been reported to exhibit worst flow distribution [10] followed by I and the distribution is best in case of Z. Therefore, a detailed study on flow characteristics of water and nanofluid as well as configurations with respect to reported data [10,18] in accordance to protocol reported by the present authors [17]. …”
Section: Computational Detailssupporting
confidence: 82%
See 1 more Smart Citation
“…U has been reported to exhibit worst flow distribution [10] followed by I and the distribution is best in case of Z. Therefore, a detailed study on flow characteristics of water and nanofluid as well as configurations with respect to reported data [10,18] in accordance to protocol reported by the present authors [17]. …”
Section: Computational Detailssupporting
confidence: 82%
“…Consequently, the non-homogeneous behavior of nanofluids was also reported [16,17] and this placed a hurdle across modeling thermo hydraulics of nanofluids in small dimensional systems such as microchannels. Singh et al [18] reported the thermal behavior of nanofluid in single microchannel and used DPM (Discrete Phase Model) model for understanding particle migration within the channel but the studies were limited to a single microchannel.…”
Section: Introductionmentioning
confidence: 99%
“…Uniform heat flux has been applied at the bottom and side walls for heat transfer cases and the top wall has been considered adiabatic. The present numerical model has been validated with respect to the published reports by Siva et al [9] and Singh et al [16]. The former study discusses in details flow maldistribution of water in parallel microchannel systems whereas the later study comprises detailed report on the thermo-hydraulic performance of nanofluids in single microchannel system.…”
Section: Computational Detailsmentioning
confidence: 64%
“…Overall there are few reports which concentrate on the modeling of flow and heat transfer characteristics of with nanofluids in microchannels but all these consider nanofluids as homogeneous single component fluids for analysis; which has been conclusive reported [16] to be an inefficient and incorrect assumption. Thorough survey of literature reveals there are no reports which try to understand the effects of flow and particle concentration distribution of nanofluids (treated as non-homogeneous twin component fluids) in parallel microchannels and its impact vis-à-vis thermal capabilities and uniformity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation